The Impact of Superior Leadership on Organizational Conflict Management: An Exploratory Study of the Opinions of a Sample of Departments in Baghdad International Airport: Pengaruh Kepemimpinan yang Unggul terhadap Pengelolaan Konflik Organisasi: Studi Eksploratif terhadap Pendapat Sejumlah Departemen di Bandara Internasional Baghdad - Wanas, Nawrs Kamil (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Leadership plays a central role in shaping organizational behavior and fostering innovation in dynamic work environments. Specific Background: Super-leadership and conflict management are increasingly recognized as critical factors in promoting a culture of innovation within organizations. Knowledge Gap: However, the interaction between super-leadership, conflict management, and organizational innovation has not been sufficiently examined in an integrated framework. Aims: This study aims to analyze the relationship between super-leadership and organizational innovation and to examine the role of conflict management in this relationship. Results: The findings indicate that super-leadership is positively associated with organizational innovation, while conflict management contributes to strengthening this relationship through effective handling of workplace disagreements. Novelty: The study provides an integrated perspective by linking leadership style and conflict management as complementary factors in fostering innovation. Implications: The results highlight the importance of leadership approaches that empower employees and manage conflict constructively to support organizational innovation and performance. Keywords: Super Leadership, Conflict Management, Organizational Innovation, Leadership Style, Workplace Dynamics Key Findings Highlights Leadership approach centered on empowerment supports innovative behavior Conflict handling mechanisms contribute to constructive organizational outcomes Combined variables provide a structured view of workplace dynamics